Effects of analgesics and antidepressants on TREK-2 and TRESK currents - Park, Hyun; Kim, Eun-Jin; Han, Jaehee; Han, Jongwoo; Kang, Dawon (The Korean journal of physiology & pharmacology, 2016)
TWIK-related K(+) channel-2 (TREK-2) and TWIK-related spinal cord K(+) (TRESK) channel are members of two-pore domain K(+) channel family. They are well expressed and help to set the resting membrane potential in sensory neurons. Modulation of TREK-2 and TRESK channels are involved in the pathogenesis of pain, and specifi c activators of TREK-2 and TRESK may be benefi cial for the treatment of pain symptoms. However, the effect of commonly used analgesics on TREK-2 and TRESK channels are not known. Here, we investigated the effect of analgesics on TREK-2 and TRESK channels. The effects of analgesics were examined in HEK cells transfected with TREK-2 or TRESK. Amitriptyline, citalopram, escitalopram, and fluoxetine significantly inhibited TREK-2 and TRESK currents in HEK cells (p<0.05, n=10). Acetaminophen, ibuprofen, nabumetone, and bupropion inhibited TRESK, but had no effect on TREK-2. These results show that all analgesics tested in this study inhibit TRESK activity. Further study is needed to identify the mechanisms by which the analgesics modulate TREK-2 and TRESK differently.